The growing phenomenon of Islamophobia in the West: its causes and targets - Ahmed, Dr. Altaf; Qadir, Abd ul (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
The phenomenon of Islamophobia has been increasingly pervasive in Western societies, manifesting through widespread prejudice, discrimination, and hostility towards Islam and its adherents. The research tries to explore its reasons and objectives. This growing trend can be attributed to several interrelated factors, including historical grievances, geopolitical conflicts, and the portrayal of Muslims in the media. Historically, the Crusades and colonial encounters sowed seeds of mistrust and enmity, which have been exacerbated by recent events such as the 9/11 attacks, the rise of extremist groups, and ongoing conflicts in the Middle East. These events have been sensationalized by the media, often depicting Islam as synonymous with terrorism and extremism, thereby reinforcing negative stereotypes and fears. The primary targets of Islamophobia are ordinary Muslim citizens who face discrimination in various aspects of life, including employment, education, and social interactions. Muslim women, particularly those who wear visible symbols of their faith such as the hijab, are especially vulnerable to hate crimes and social exclusion. Additionally, Islamic places of worship and cultural centers have been targeted, further marginalizing Muslim communities.